"Judaism Intertwines with Worldly Good": A Qualitative Study on Religious Rehabilitation Programs in the Israeli Prison Service - Haviv, Noam; Shoham, Efrat; Hasisi, Badi; Weisburd, David; Toren-Rozanski, Yaara (International Journal of Criminology and Sociology, 2022)
Background: Religion with its religious institutions has played a key role in shaping punishment and rehabilitation of offenders throughout history. The aim of these programs is to transform a person spiritually and lead them to intra-personal changes on the religious level by prompting repentance or the reaffirmation of one's faith. Objectives: We present qualitative findings from an evaluation of two religious programs operating in the Israeli Prison Service: The Torah Rehabilitation Program (TRP) that functions as a religious community within prison walls, and the Torah Study Program (TSP) in which prisoners participate faith-based studies four hours a day. The main research question that led the researchers was how Judaism provides opportunities for prisoner’s rehabilitation. Method: This research is a qualitative study that includes seven interviews with seven Rabbis who work in the Israeli Prison Service and lead the religious programs. The interviewees were involved in the formulation and implementation of the religious correctional programs. Results: The interviewees have raised a link between Jewish beliefs and practices, including atonement, and the foundations of prisoners’ rehabilitation. Among the themes that have been raised: promoting moral action; giving prisoners a second chance; providing opportunities for repentance and atonement; supervision; placing emphasis on behavioral norms; focusing on belonging and commitment to a community; working alongside Torah; learning and providing a unique response to each individual according to their characteristics and needs. Conclusions: The emerging themes raised in the interviews correspond well with theoretical ideas found in the field of corrections in general and in positive criminology in particular